Comunicação organizacional e gestão universitária: análises e propostas para a UFPR Litoral - Fernandes, William Leal Colaço (2019)
Universities are formal organizations and stand out for the high degree of complexity in their nature, processes and structures. In them, it becomes more difficult to converge the alternatives to a common end, due to the diversity of existing variables. The organizations that are part of our daily lives involve and are dependent on the participation of people. It is the communication that makes the interaction and the balance between the different parts of the system that is the organization. In this sense, communication plays a fundamental role in the functioning of organizations. Understanding how communication works and knowing how to manage it can improve the overall system. Thus, the objective of the research is to analyze the organizational communication process of the Coastal Sector of the Federal University of Paraná (UFPR) and propose adjustments in the way communication is carried out in the institution, improving the flow of information and benefiting all the academic community. The research consists of a case study and is characterized as an exploratory-descriptive study. The data were collected through an electronic questionnaire, applied to the technical administrative and teaching staff, as well as semi-structured interviews with the institution's managers. Analyzing the Coastal Sector of UFPR from the perspective of integrated communication, there were identified failures in the administrative and internal communication that related to the internal communication flows and the visual signaling of the sector and in the marketing communication, referring to the image that the institution reflects to the external public. As proposals for improvements aimed at meeting these demands, changes were suggested in the internal communication system with the servers, through the modernization of Informes Litoral, the creation of an internal app to the servers and a visual signage project. In addition to a more intensive work in social media and the creation of a strategic communication plan for the UFPR Litoral, aiming to work the image of the institution in the local community. It is hoped by this study to provide communication grants so that it is possible to establish supporting structural pillars in which managers can base themselves to make the necessary changes.